A Cluster Randomized-Controlled Trial of the Impact of the Tools of the Mind Curriculum on Self-Regulation in Canadian Preschoolers - Solomon, Tracy; Plamondon, Andre; O’Hara, Arland; Finch, Heather; Goco, Geraldine; Chaban, Peter; Huggins, Lorrie; Ferguson, Bruce; Tannock, Rosemary (Frontiers in Psychology, 2018)
Early self-regulation predicts school readiness, academic success, and quality of life in adulthood. Its development in the preschool years is rapid and also malleable. Thus, preschool curricula that promote the development of self-regulation may help set children on a more positive developmental trajectory. We conducted a cluster-randomized controlled trial of the Tools of the Mind preschool curriculum (Tools; clinical trials identifier NCT02462733). Previous research with Tools is limited, with mixed evidence of its effectiveness. Moreover, it is unclear whether it would benefit all preschoolers or primarily those with poorly developed cognitive capacities (e.g. language, executive function, attention). Objectives were to ascertain whether the Tools program, that targets self-regulation through imaginative play and self-regulatory language, leads to greater gains in self-regulation compared to Playing to Learn (YMCA PTL), another play based program that does not target self-regulation specifically, and whether the effects were moderated by children’s initial language and hyperactivity/inattention. Two hundred and sixty 3- to 4- year-olds attending 20 largely urban daycares were randomly assigned, at the site level, to receive either Tools or YMCA PTL (the business-as-usual curriculum) for 15 months. We assessed self-regulation at pre-, mid and post intervention, using two executive function tasks, and two questionnaires regarding behaviour at home and at school, to capture development in cognitive as well as socio-emotional aspects of self-regulation. Fidelity data showed that only the teachers at the Tools sites implemented Tools, and did so with reasonable success. We found that children who received Tools made greater gains on a behavioural measure of executive function than their YMCA PTL peers, but the difference was significant only for those children whose parents rated them high in hyperactivity/inattention initially. The effect of Tools did not vary with children’s initial language skills. We suggest that, as both programs promote quality play and that the two groups fared similarly well overall, Tools and YMCA PTL may be effective curricula choices for a diverse preschool classroom. However, Tools may be advantageous in classrooms with children experiencing greater challenges with self-regulation, at no apparent cost to those less challenged in this regard.